Saturated Spectroscopy and Unsaturated Spectroscopy Comparative Study on Malignant and Benign Human Cancer Cells and Tissues with the Passage of Time under Synchrotron Radiation - Alireza Heidari (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2018)
In the current study, we have experimentally and comparatively investigated and compared malignant human cancer cells and tissues before and after irradiating of synchrotron radiation using Saturated Spectroscopy and Unsaturated Spectroscopy, respectively.